Tuberculosis Transmission in a Primary School and a Private Language School. An Estimation of Infectivity - Debulpaep, Sara; Dreesman, Alexandra; Dirix, Violette; Toppet, Veronique; Wanlin, Maryse; Geysens, Lies; Arrazola de Oñate, Wouter; Fauville, Maryse; Mascart, Françoise; Levy, Jack; Mouchet, Françoise (Frontiers in Pediatrics, 2020)
Introduction: Belgium is a country with low incidence of tuberculosis (TB) and a very low number of TB cases in children. Children in contact with an adult smear-positive TB case are at high risk of transmission. Early diagnosis is important as young children have a significant predisposition of developing TB disease. In this paper, we describe two outbreaks after exposure to, respectively, two teachers with smear-positive pulmonary TB: one in a primary school, a nursery teacher, and another in a private language school. Methods: An exposure investigation was carried out in both index cases household and school, according to the stone-in-the-pond principle. The tuberculin skin test (TST) was used a screening tool. The time elapsed between TB diagnosis in the index case and contact investigation was, respectively, 1 and 3 weeks. If this initial test was negative, it was repeated after a “window period” of ≥8 weeks. Results: Index cases showed a transmission rate of, respectively, 13 and 40% in their classes at school, defined as casual contacts. The proximity of contact increased the risk of infection. TB disease was observed in, respectively, 4 and 11% of all the casual contacts; all of them were children younger than 5 years old. TB-infected and children with active TB disease had good compliance with recommended treatment. Uptake of chemoprophylaxis during the “window period” was poor, respectively, only 32–42%, in children under 5 years with an initially negative TST. Discussion: The World Health Organization recommends to screen all young children (<5 years old) who have close contact with a person affected by pulmonary TB and to initiate Latent tuberculosis infection treatment even before infection can be demonstrated, after ruling out active TB disease. Despite this knowledge, a small percentage of the children younger than 5 years with no proof of infection was treated with the proposed chemoprophylactic treatment, in both cases. Conclusion: This exposure investigation of two teachers detects high transmission among family contacts and school casual contacts. Recommendations for chemoprophylactic treatment in children <5 years showed low compliance, reflecting the difficulty of communication to staff, parents, and children in a school outbreak. It is essential to develop a new approach for this vulnerable group of patients. This approach could be improved, applied, and evaluated by National TB Control Programs, involving public and private health services. Public health authorities play a role in raising public awareness about the risks of TB for young children.